Inflammation, endothelial dysfunction, and platelet activation in patients with chronic kidney disease: the chronic renal impairment in Birmingham (CRIB) study. - Landray, M; Wheeler, D; Lip, G; Newman, D; Blann, A; McGlynn, F; Ball, S; Townend, J; Baigent, C (2004)
BACKGROUND: Studies in the general population suggest that low-grade inflammation, endothelial dysfunction, and platelet activation are associated with an increased risk of cardiovascular events. METHODS: Markers of inflammation, endothelial dysfunction, and platelet activation were measured in 334 patients with chronic kidney disease (serum creatinine >1.47 mg/dL [>130 micromol/L] at screening) and compared with 2 age- and sex-matched control groups, 1 comprising 92 patients with coronary artery disease and the other comprising 96 apparently healthy individuals with no history of cardiovascular or kidney disease. RESULTS: There was evidence of low-grade inflammation in the chronic renal impairment group compared with healthy controls, with higher concentrations of C-reactive protein (3.70 versus 2.18 mg/L, P < 0.01) and fibrinogen (3.48 versus 2.67 g/L, P < 0.001) and lower serum albumin concentration (41.8 versus 44.0 g/dL [418 versus 440 g/L], P < 0.001). More severe renal impairment was associated with a trend towards higher fibrinogen and lower albumin concentrations (both P < 0.001), although there was no association with higher C-reactive protein level. As compared to healthy controls, plasma von Willebrand factor (142 versus 108 IU/dL, P < 0.001) and soluble P-selectin concentrations (57.0 versus 43.3 ng/mL, P < 0.001) were also higher in the chronic renal impairment group. More severe renal impairment was associated with a trend towards higher levels of von Willebrand factor (P < 0.001) and of soluble P selectin (P < 0.05). CONCLUSION: This cross-sectional analysis demonstrates that chronic kidney disease is associated with low-grade inflammation, endothelial dysfunction, and platelet activation, even among patients with moderate renal impairment.